2012
DOI: 10.1093/geronb/gbs116
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Dementia Caregiver Depressive Symptoms in a Population: The Cache County Dementia Progression Study

Abstract: These results suggest that depression may be less prevalent in populations of dementia caregivers than in clinic-based samples, but that the correlates of depression are similar for both population and convenience samples. Interventions targeting individuals with small support networks, emotion-focused coping styles, poorer health, low quality of life, and those caring for persons with higher numbers of behavioral problems need development and testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 36 publications
1
32
0
3
Order By: Relevance
“…Specifically, Wishful Thinking and Blames Self coping strategies were associated with overall higher levels of anxiety in caregivers, which was also higher with longer duration of dementia in the care recipient. The former finding coincides and strengthens our previous cross-sectional study that linked Wishful Thinking with higher symptoms of depression among caregivers (Piercy et al, 2012). It may be prudent to identify, and target for intervention, caregivers using Wishful Thinking and Blames Self as a primary coping strategies so as to improve outcomes of caregiver psychological health.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Specifically, Wishful Thinking and Blames Self coping strategies were associated with overall higher levels of anxiety in caregivers, which was also higher with longer duration of dementia in the care recipient. The former finding coincides and strengthens our previous cross-sectional study that linked Wishful Thinking with higher symptoms of depression among caregivers (Piercy et al, 2012). It may be prudent to identify, and target for intervention, caregivers using Wishful Thinking and Blames Self as a primary coping strategies so as to improve outcomes of caregiver psychological health.…”
Section: Discussionsupporting
confidence: 91%
“…We also found that, cross-sectionally, rates of depressive symptoms were lower in caregivers who used less wishful thinking but more problem-focused coping strategies. (Piercy et al, 2012). The purpose of this study was to examine the association of caregivers’ coping strategies with changes over time in their mental and physical health.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with previous research identifying problematic behaviors as a correlate of depression and self-reported health. 2,54,55 However, either the improvements in sleep quality and stress were not enough of a change or did not occur over a long enough time period, or, because the symptoms of depression were low for the sample (the mean CESD score fell below 16), the change in stress and sleep did not coincide with a change in depression.…”
Section: Discussionmentioning
confidence: 99%
“…Literatürde demans; bellek, dil, soyut düşünme, problem çözme, yönelim gibi bilişsel işlevlerde ilerleyici yıkım ile karakterize, sosyal işlevsellik ve entelektüel kapasitede gerileme ile devam eden bir hastalık tablosu olarak tanımlanmaktadır. [12][13][14] Katılımcılar bakım vermeyi; çoğunlukla bakılan kişinin her şeyinden sorumlu olma olarak tanımlamışlardır. Williams bakım vermeyi; bakıma muhtaç birisine fiziksel, zihinsel, duygusal, sosyal ve ekonomik yönden bakımını sağlama olarak tanımlamıştır.…”
Section: Discussionunclassified
“…Dolayısıyla demanslı bireylere bakım veren yakınlarının yaşamları günlük yaşamlarından sosyal yaşamlarına kadar her yönüyle etkilenmektedir. [1,14,17,19,24] Çalışmada, katılımcılar bakım verirken yaşanılan zorluklarla baş etmede çoğunlukla dua etmeyi tercih ettiklerini ifade etmiştir. Demans bakımı zor ve bakım vericiye yükü oldukça fazla olan bir hastalık tablosudur.…”
Section: Discussionunclassified